2011
DOI: 10.1007/s00265-011-1169-3
|View full text |Cite
|
Sign up to set email alerts
|

Can faecal glucocorticoid metabolites be used to monitor body condition in wild Upland geese Chloephaga picta leucoptera?

Abstract: The measurement of faecal glucocorticoid metabolites is used as a non-invasive technique to study stress in animal populations. They have been used most widely in mammals, and mammalian studies have also treated issues such as sample stability and storage methods. In birds, faecal corticosterone metabolite (CM) assays have been validated for a small number of species, and adequate storage under field conditions has not been addressed explicitly in previous studies. Furthermore, while it is well-established tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…Furthermore, the allocation of body resources into reproduction (loss of body condition) was associated with increased plasma concentrations of glucocorticoids toward the end of reproduction among A. childreni. Likely due to the role of glucocorticoids in energy mobilization, a similar negative relationship between body condition and glucocorticoids has been documented in other reptiles (Moore et al 2000), birds (Gladbach et al 2011), and mammals (Cabezas et al 2007). Yet future research is required to clarify trade-offs between morphology and self-maintenance in A. childreni during reproduction.…”
Section: Discussionmentioning
confidence: 84%
“…Furthermore, the allocation of body resources into reproduction (loss of body condition) was associated with increased plasma concentrations of glucocorticoids toward the end of reproduction among A. childreni. Likely due to the role of glucocorticoids in energy mobilization, a similar negative relationship between body condition and glucocorticoids has been documented in other reptiles (Moore et al 2000), birds (Gladbach et al 2011), and mammals (Cabezas et al 2007). Yet future research is required to clarify trade-offs between morphology and self-maintenance in A. childreni during reproduction.…”
Section: Discussionmentioning
confidence: 84%
“…Our finding that one marker of stress (FGM concentrations) is linked to body weight (as a proxy for body condition) but not the other (H/L ratio) is somewhat surprising, since we expected both of these markers of long-term stress to be negatively correlated to body condition. However, at least the link between FGM concentrations and body weight is not unexpected, since the relationship between GCs and body condition has been shown several times before in other species [43,78]. GCs are involved not only in an animals' stress response, but also in energy mobilisation, fat metabolism, and muscle catabolism, and these factors can negatively influence body condition.…”
Section: Discussionmentioning
confidence: 93%
“…In the present study, we investigate variations in two markers of stress-FGM concentrations and H/L ratios-for the first time in Asian elephants and link these measures to changes in body condition (determined by body weight). Body condition (or body weight as a proxy) is often used as a physical marker of welfare, and it has been suggested that FGM concentrations can be a valuable tool to monitor body condition or health [43]. Our aim was therefore to test if our two markers of stress would be linked to body weight in Asian elephants as well.…”
Section: Introductionmentioning
confidence: 99%
“…We found that the hormone metabolite levels declined with an increase in the BCS from 1 to 3. Although cause and effect remain unclear, several other studies also report a negative relationship of fGCM with body condition in birds, amphibians and reptiles, thereby emphasizing the role of glucocorticoid hormones in energy mobilization ( Moore and Jessop, 2003 ; Husak and Moore, 2008 ; Gladbach et al , 2011 ). Cortisol or glucocorticoid is a gluconeogenic hormone which produces glucose by promoting the breakdown of muscle, bone, and connective tissues; thus, elevated levels of cortisol during stress will break down these structural tissues resulting in inhibition of protein synthesis, elevated energy mobilization, and reduction in body mass ( Kitaysky et al , 1999 ; Landys et al , 2006 ; Cabezas et al , 2007 ; Schakman et al , 2013 ).…”
Section: Discussionmentioning
confidence: 99%